INDICADORES DE SAÚDE DE PESSOAS COM CONDIÇÕES CRÔNICAS DE HIPERTENSÃO ARTERIAL E DIABETES MELLITUS NO MARANHÃO - SOEIRO, Vanessa Moreira da Silva (2017)
Noncommunicable Chronic Diseases (NCD), especially Systemic Arterial Hypertension (SAH) and Diabetes Mellitus (DM) are a worldwide problem, related to high morbidity and mortality rates in several countries. They are still the greatest burden of the health systems in the world impacting those with chronic conditions, their families and society. In this context, the monitoring and evaluation of health indicators for the treatment and control of SAH and DM is fundamental. This research aimed to analyze health indicators of people with chronic conditions of arterial hypertension and diabetes mellitus in a historical series of 17 years in the State of Maranhão, registered in the Basic Health Care Information System (SIAB) and in HiperDia System. This study is descriptive and observational with a quantitative approach, using secondary data with methodologically based in the Theory of Practical Intervention of Nursing in Collective Health (TIPESC). The findings indicated an increase in the enrollment of people with SAH and DM in SIAB and in SIS-HiperDia in Maranhão. However, the enrollment of people with both NCDs in SIS-HiperDia occurred in an anomalous way, not following tendency of growth or decline. There was also a discrepancy in the quantitative registration of both systems. The macro-region of São Luís had the highest percentages of people with SAH and DM in most of the years, in SIAB and SIS-HiperDia, and the lowest percentage were recorded in the macro-region of Balsas. As for the profile of the enrollees in the SIS-HiperDia, there was a prevalence of the NCD studied in the female sex and in the age group of 60 to 79 years. The stroke complication and the sedentary risk factor were the most frequently mentioned. It was identified that the number of registered in the SIAB was below the estimate of individuals with the two diseases in the State. The state Maranhão reached a satisfactory average number of visits per person with both pathologies, being in most of the years above that established by the Ministry of Health, however, the professionals registered the productivity in the SIAB and did not feed satisfactorily the SIS-HiperDia. The follow-up by the ACS reached percentages above 90% for the two NCDs. The epidemiological indicators - specific mortality rate for DM and prevalence rates of SAH and DM - increased over the 17 years analyzed. It is concluded that even with the implementation of Primary Health Care actions, since 1998, with a gradual increase in the coverage and growth of enrollment and follow-up of people with SAH and DM, there was no reduction in the morbidity and mortality of the two NCDs in Maranhão.